A Dictionary Of Mining, Mineral, And Related Terms - Preface (The National Institute for Occupational Safety and Health (NIOSH), 1968)
This dictionary is published by the Bureau of Mines as a contribution to the mining and mineral literature in the belief that it will fill a recognized need. Several attempts have been made over the years to revise Albert Fay's Glossary of the Mining and Mineral Industry which first appeared in December of 1918. Frank L. Hess of the Bureau of Mines worked on a revision, but his untimely death prevented its completion. Subsequently, the writer was employed to compile and edit this dictionary in cooperation with the technical staff of the Bureau of Mines. Fay's glossary contained about 18,000 terms with 27,000 definitions; the present compilation contains about 55,000 terms with approximately 150,000 definitions. These terms are of both a technical and local nature, and they apply to metal mining, coal mining, quarrying, geology, metallurgy, ceramics and clays, glassmaking, minerals and mineralogy, and general terminology. Petroleum, natural gas, and legal mining terminology, unless of a general nature, has been excluded, as has been foreign terminology where there is an English equivalent. Several thousand Spanish-American mining terms that appeared in Fay's compilation have been removed to make way for the thousands of new English terms that have evolved over the years. Those Spanish-American and Mexican terms still used in the Southwestern United States have been retained.